O uso do ??lcool e a polifarm??cia no idoso - Melo, Danielle Alves de (2016)
The aging of the world population is a challenge for health systems. Faced with the aging profile change, with the elderly population steadily increasing, it is necessary strategies to ensure healthy aging. One of the strategies for the aging quality is the use of various drugs, known as polypharmacy. However, the drugs, besides interact with each other, may interact with other factors such as consuming alcohol. The objective was to evaluate the concomitant use of poly pharmacy and alcohol by elderly of the Granja do Torto-D.F neighborhood, through a questionnaire of MEEN and another one structured. It is concluded that from the 202 elderly respondents, 130 (64%) use polypharmacy. However among those, only 16 people (8%) make concomitant use of alcohol. The low percentage may be related to the assistance that the elderly receive in the local health center, with the attendance of a multidisciplinary team. The constant monitoring of the public and the increase awareness of health condition and the risks of consuming alcohol and various drugs, enables the reduction of risks to the health and helps to maintain healthy habits.